Analysis of Technology Acceptance (pedulilindungi) as Citizens Health in Kelurahan Air Hitam of Samarinda City - Aidillah, Muhammad Rafli; Suwanto, Suwanto; Supriyatno, Andik (Institut Teknologi Kesehatan Dan Sains Wiyata Husada Samarinda, 2022)
The Penduli Lindungi application is an application designed as health information that was launched during the Covid 19 pandemic. This study aims to analyze the acceptance of the application technology of care to protect as citizens of health in the Black water of Samarinda City. Research methods used by quantitative types of research with a cross- sectional study approach. The population and samples were all residents in the Bersama complex in the black water village who used the peduli lindungi app as many as 60 people. The acceptance of the Peduli Lindungi application is quite accepted by the public due to the urgency of use and the transformation from a change in community behavior to a digital society so that in the future the development of the peduli lindungi application will be very useful as a digital public health information center .